A Case Study of the Holistic Education Approach in Rajasthan - Dr. Pawan Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The present research intends to assess the execution of comprehensive instruction and identify the elements that assist or ‘hinder it in’ Rajasthan’s schools. This study's methodology involves ‘descriptive qualitative’ using an empirical research technique within the educational institution of Rajasthan. The method used to acquire the information included secondary surveying and reviewing earlier reports. Reduced presentation of information and conclusion-making were used throughout the statistical analysis. The findings suggested ‘the state's high school’ offered ‘a holistic education’ including comprised schoolwork outside of school, student entrepreneurial, and environmental care programs. Three separate instructional centers, the skilled educators, the instructional method, the buildings plus amenities, school management, including school culture comprised all contributing elements to the complete schooling. ‘The small number’ of residential instructors plus the hefty operating expenses were the deterrents, however. The findings imply that in order to develop clever and competent pupils, every institution ought to provide proper opportunities for professional ‘learning resources’ for the entire community.
Keywords: Holistic education; student development; NEP; development plan; learning features; learning resources